Patterns of ecosystem development in glacial foreland chronosequences: a comparative analysis of Chile and New Zealand. Issue 2 (2nd April 2016) - Pérez, CA; Aravena, JC; Silva, WA; McCulloch, R; Armesto, JJ; Parfitt, R
ABSTRACT: After catastrophic disturbances, depleted substrates are readily colonised by organisms that capture nitrogen from the atmosphere and extract phosphorus from minerals. Our main objective was to compare the pattern of ecosystem development following deglaciation in Chile and New Zealand. Results show a similar pattern of C and N accumulation and decline in soil chronosequences, similar decline in biological nitrogen fixation (BNF) and similar δ 15 N-enriched signal at later stages, providing evidence for the existence of progressive, maximal and retrogressive phases of ecosystem development. However, contrasting patterns between Chilean and New Zealand sites are evident during the progressive phase, when higher C/N, C/P and N/P ratios are found in soils and leaves in Chile than in New Zealand, suggesting a higher nutrient limitation and nutrient use efficiency in the former. Highest rates of BNF were found at the early stages of both the Chilean and New Zealand chronosequences. Contrasting patterns across regions were the lack of a decline in soil total P, and the depleted values in soils of 15 N during the progressive phase in the Chilean chronosequences, but enriched values, suggesting an open nitrogen cycle, during retrogression in both the Chilean and the New Zealand chronosequences. Overall, these results provide evidence for the existence of retrogression with ecosystem development in the sub-Antarctic region of the world, even when comparing contrasting biomes, climatic regions and geological substrates.